As incubadoras tecnológicas de cooperativas populares e a proposta de formação integral dos institutos federais de educação, ciência e tecnologia: aproximações práticas e conceituais - Guergoletto, Gustavo Bigetti (2025)
This study analyzes the theoretical and practical approaches to the articulation between Technological Incubators of Popular Cooperatives (ITCPs) and the perspective of integral education within the Federal Institutes of Education, Science, and Technology (Ifs), aiming at the development of a technological education aligned with the critical formation of students. The research is based on the hypothesis that ITCPs, aligned with the principles of Solidarity Economy, promote critical educational practices that contribute to students’ education. The study is contextualized within the challenges posed by the flexible accumulation regime, such as job precariousness, the valorization of individualism over collectivism, and the increasing devaluation of human, social, and critical education. The theoretical framework draws on the Critical Theory of Technology, the values of the Solidarity Economy and its incubators, as well as contributions from Marx and Gramsci regarding education and labor, which have informed the educational proposal of the Ifs.This exploratory and descriptive research adopts a predominantly qualitative approach. Data collection involved bibliographic, documental, and field research, focusing on the activities carried out by two ITCPs linked to the Ifs between 2019 and 2022. Selection criteria for the incubators included alignment with the Solidarity Economy, a minimum of 12 months of operation, and the provision of integrated secondary education on campus. The Technological Incubator of Solidarity Economy of IFRJ Niterói campus (ITES-Niterói) and the Technological Incubator for the Strengthening of Solidarity Economic Enterprises of IFRN Natal Zona Norte campus (IFSOL/ZN), the objects of the field research, enabled the gathering of information through semi-structured interviews with teachers and graduates of integrated secondary education. Additionally, projects and activities developed by these incubators were analyzed, highlighting their formative potential in the human, scientific-technological, and professional dimensions of integral education. Discursive Textual Analysis supported the identification of these dimensions and the analysis of the collected data. The results indicate that ITCPs contribute to integral education across all its dimensions by integrating popular and academic knowledge, fostering cooperation and self-management, and encouraging students’ critical thinking. Furthermore, the findings show how these incubators operate at the interface between teaching, research, and extension, promoting socially engaged technological solutions. It was identified that Solidarity Technoscience, embedded in the practices of these incubators, proposes a science oriented towards local needs and sustained by community participation, finding a fertile ground for its development within the ITCPs. The study concludes that ITCPs strongly align with the principles of Solidarity Economy and the educational objectives of Ifs, reinforcing the proposal of integral and critical education in these institutions. However, challenges such as funding limitations and tensions between emancipatory values and market demands are highlighted as barriers to be overcome. This study emphasizes the need for public policies that promote the consolidation of ITCPs within Ifs, recognizing them as strategic tools for sustainable development and the critical and civic education of individuals.